2021
DOI: 10.1007/s00521-020-05626-8
|View full text |Cite
|
Sign up to set email alerts
|

A review on COVID-19 forecasting models

Abstract: The novel coronavirus (COVID-19) has spread to more than 200 countries worldwide, leading to more than 36 million confirmed cases as of October 10, 2020. As such, several machine learning models that can forecast the outbreak globally have been released. This work presents a review and brief analysis of the most important machine learning forecasting models against COVID-19. The work presented in this study possesses two parts. In the first section, a detailed scientometric analysis presents an influential too… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(151 citation statements)
references
References 85 publications
(93 reference statements)
1
125
0
2
Order By: Relevance
“…Moreover, several attempts are considered modifications of conventional compartmental models for more general and efficient forecasting (e.g., [9,10]). A review of COVID-19 forecasting models is in [11]. In this review, it was shown that deep learning models can reach to human expert level but it requires a relatively large amount of training data.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several attempts are considered modifications of conventional compartmental models for more general and efficient forecasting (e.g., [9,10]). A review of COVID-19 forecasting models is in [11]. In this review, it was shown that deep learning models can reach to human expert level but it requires a relatively large amount of training data.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, the academic literature has witnessed a vast surge of modelling studies. Existing reviews highlight the importance of compartmental models of COVID-19, in connection with other models based on time series forecasting and machine learning [ 12 , 13 ]. Compartmental models mathematically encode known and emerging information about the transmission dynamics of the disease and have been locally applied across numerous contexts around the world, including major sites of COVID-19 transmission like China, India, Brazil, the United States, and the United Kingdom [ 14 – 18 ].…”
Section: Related Workmentioning
confidence: 99%
“…Different models have been designed to predict future positive/death cases [7][8][9][10][11][12]. Machine learning and other artificial intelligence techniques are expected to provide better data analysis and lead to its understanding as well as provide more accurate prediction models [11,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%